Bud-Poplar-Extract-Embedded Chitosan Films as Multifunctional Wound Healing Dressing - Carla Russo; Miranda Piccioni; Maria Laura Lorenzini; Chiara Catalano; Valeria Ambrogi; Rita Pagiotti; Donatella Pietrella (Molecules, 2022)
Wounds represent a major global health challenge. Acute and chronic wounds are sensitive to bacterial infection. The wound environment facilitates the development of microbial biofilms, delays healing, and promotes chronic inflammation processes. The aim of the present work is the development of chitosan films embedded with bud poplar extract (BPE) to be used as wound dressing for avoiding biofilm formation and healing delay. Chitosan is a polymer with antimicrobial and hydrating properties used in wound dressing, while BPE has antibacterial, antioxidative, and anti-inflammatory properties. Chitosan-BPE films showed good antimicrobial and antibiofilm properties against Gram-positive bacteria and the yeast Candida albicans. BPE extract induced an immunomodulatory effect on human macrophages, increasing CD36 expression and TGFβ production during M1/M2 polarization, as observed by means of cytofluorimetric analysis and ELISA assay. Significant antioxidant activity was revealed in a cell-free test and in a human neutrophil assay. Moreover, the chitosan-BPE films induced a good regenerative effect in human fibroblasts by in vitro cell migration assay. Our results suggest that chitosan-BPE films could be considered a valid plant-based antimicrobial material for advanced dressings focused on the acceleration of wound repair.